The records management program of the Department of Agrarian Reform - Villania, Vaneth Leigh V.; Rey, Emma M.; Department of Agrarian Reform (Quezon City School of Library and Information Studies, University of the Philippines Diliman, 2010)
This study evaluated the records management program of the Department of Agrarian Reform using the National Archives' Guidelines in Records Management or the NAP General Circular No. 1 and NAP General Circular No. 2. Based on Saffady's (2004) Records Management Components, the following were evaluated 1. Records retention; 2.Compliance with Laws and Regulations; 3. Cost-Effective Management of Inactive Records; 4. Organization and Retrieval of Active Records; 5. Protection of Vital Records.
The researcher employed a descriptive approach in the study. Three methods of data collection were used: semi-structured interview and self-completion questionnaires with two Records Offices and Records Custodians; ocular visits in the Department of Agrarian Reform Central Office in Quezon City, particularly in the Records Management Division (RMD); and use of primary and secondary resources. Findings include: 1. DAR has yet to formulate a Records Management Manual specifying definite guidelines in Records Creation, Use and Maintenance, and Storage.2. DAR has a centralized system of managing active records. Each DAR office has a Records Custodian who tends to the active files. 3. DAR-RMD takes hold of all the inactive records of DAR that are transferred from the different DAR offices nationwide. The RMD uses the Function-Subject-Alphabetical Cataloguing System or FSACS in organizing its records, a filing sysem which NAP suggests to most of the government agencies. 4. DAR-RMD houses the vital records in its Records Storage Center. Most of DAR's vital records are land cases and the originating DAR office usually has a copy of these records. Vital records have restricted access to the internal clients (DAR employees) and even more to the external clients. 5. DAR's first Records Disposition Schedule (RDS) was formulated way back in 1983 with the help fo the National Archives of the Philippines. Pursuant of the Rep. Act No. 9470, DAR has updated the RDS to Comprehensive Records Disposition Schedule in 2007. DAR strictly complies with its RDS, especially in Records Retention.
Vita.
Thesis (Bachelor of Library and Information Science)
Keywords: Records -- Management -- Philippines